Vascular Behçet's disease: a comparative study from Turkey and France - DİRESKENELİ, RAFİ HANER; ALİBAZ ÖNER, FATMA (My University, 2022)
Objective Vascular Behçet’s disease (VBD) is a systemic vasculitis involving both arterial and venous vessels of all sizes and occurring in up to 40% of patients with BD. VBD is the main cause of mortality in BD. Although commonly seen around the Mediterranean region, comparative studies in VBD are lacking. We aimed to compare the course and therapeutic approaches of VBD in two large cohorts from Turkey and France. Methods We included 291 VBD patients (female/male:63/228, mean age: 41.2±11.3 years) who were followed up in the Department of Internal Medicine and Clinical Immunology at Pitié-Salpêtrière Hospital, Sorbonne University, Paris, France (n=131) and Rheumatology Division of Marmara University School of Medicine, Istanbul, Turkey (n=160). All clinical and demographical data were acquired from patient charts retrospectively. Results Smoking, family history for BD, HLA-B*51 presence and pathergy positivity were significantly higher in Turkish patients (TR), while neurologic involvement was more prominent in the French (FR) group. After a median follow-up of 77 months, 562 vascular events occurred including 440 venous events, 115 arterial events and 7 cardiac thrombi. In 79 (29%) patients, first vascular event developed before BD diagnosis and for 77 (28%) of them, vascular involvement was the presenting sign of the disease. First relapse developed in 130 (44.7%) patients after median 24.5 (1-276) months of follow-up (TR: 46.3% (n=74), FR: 42.7% (n=56), p=0.56). Survival graph revealed that FR cohort has 1.64 times increased recurrent event risk compared to TR cohort (HR=1.64 (1.1-2.44), p=.014) and although did not reach to statistical significance, IS treatment after the first vascular event decreased further vascular events (HR= 0.66 (0.43-1.01, p=.057). Conclusion Almost half of patients relapsed of VBD within 2 years after the first vascular event. Immunosuppressants decrease VBD relapses.
Keywords: vascular Behçet’s disease; relapse; treatment; immunosuppressives; anti-coagulation